2017
DOI: 10.2139/ssrn.2902717
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Gender Differences in Confidence and Overconfidence in Math

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 17 publications
2
9
0
3
Order By: Relevance
“…Studies of gender differences in confidence levels among students in other disciplines found that lower self-ratings of abilities and confidence among females compared to males mirrored the disparities in gender socialization that resulted from discriminatory social conditions. 31,32 They also found that the difference in confidence between the genders was more a reflection of overconfidence among males than lesser confidence among females. The role of gender norms and socialization impacting dental training is an important area of research that needs more examination.…”
Section: Discussionmentioning
confidence: 97%
“…Studies of gender differences in confidence levels among students in other disciplines found that lower self-ratings of abilities and confidence among females compared to males mirrored the disparities in gender socialization that resulted from discriminatory social conditions. 31,32 They also found that the difference in confidence between the genders was more a reflection of overconfidence among males than lesser confidence among females. The role of gender norms and socialization impacting dental training is an important area of research that needs more examination.…”
Section: Discussionmentioning
confidence: 97%
“…As a further explanation, they suggest that men and women differ in the way how they acquire financial knowledge, even if they dispose of the same skills and opportunities to learn. These differences may be related to the frequent observation that women self-report lower levels of confidence when it comes to learning mathematics, which may again be driven by cultural and societal norms (Cho, 2017). As Gneezy et al (2003) have shown, women tend to underestimate their actual abilities, especially when competing with males.…”
Section: The Role Of Gender In the Decision-making In Householdsmentioning
confidence: 99%
“…Of particular interest are experiences with parents, such as the level of autonomy that parents allow their child to have and the level of maturity they expect from their child, and socialization with peers in daycare and school. Moreover, other work has pointed to the role of children's experiences with how their successes are praised or undermined by parents and society at large (Cho, 2017). The current work as well as these proposed future directions paint a more comprehensive picture of the development of non-ability-based confidence beyond just personality differences, which has been the focus of past work.…”
Section: Future Directionsmentioning
confidence: 80%
“…Lingel and colleagues (2019) demonstrate that students with lower achievement levels in math are more likely to be overconfident in the same domain. Cho (2017) similarly showed that both males and females with higher math ability have lower levels of overconfidence. Each of these studies, however, was cross-sectional and thus, the current paper adds to this body of work by demonstrating a developmental trajectory of achievement that predicts non-ability-based confidence.…”
Section: Potential Explanations Of Divergent Findings For Math and Readingmentioning
confidence: 91%